IMPROVING TRADITIONAL MARKET SUSTAINABILITY IN THE INDUSTRIAL 4.0 ERA THROUGH IMPULSIVE BUYING STRATEGY: A CASE IN EAST JAVA, INDONESIA - Handayani, Wiwik; Iryanti, Endang; Safeyah, Muchlisiniyati; Hardjanti, Susi (International Journal of Supply Chain Management, 2019)
In the industrial 4.0 era, the issue of impulsive buying to maintain an increased purchases has become ever more attractive to be explored. The major ground is the existence of technology that stimulates consumer s interest to products in sight. A more eye-catching display, will escalate consumers' desire to shop. Many modern markets have applied technology to intensify consumer purchases, however, in traditional markets such practices seem to be unfamiliar. For this reason, this study examined variables that affect impulsive buying behavior in traditional markets, employing factors that encourage impulsive buying in the modern market to the traditional markets. Population in this study was consumers of traditional markets in East Java, with purposive sampling technique, and respondents amounting to 400 people. The first research procedure was an experiment, controlling four variables, namely the environment, discount price, payment procedures and facility, continued by spreading questionnaires to respondents. Afterwards, the data was being analyzed using PLS (Partial Least Square). The results of the analysis displayed that the model was acceptable which explained that variable such as environment, discount price, payment procedures and facility affect impulsive buying in traditional markets. Thus, it may be concluded that impulsive buying behavior in modern markets and traditional markets is similar. When discount prices contributed the greatest influence on the traditional markets, in modern markets, the impact was even more profound.